2021
DOI: 10.1002/er.6501
|View full text |Cite
|
Sign up to set email alerts
|

Comparative density functional theory study of carbon formation and removal mechanism on Rh modified Ni‐based catalyst in theCH4/CO2reforming

Abstract: Summary Rh catalyst shows promising performance for coke resistance in the CH4/CO2 reforming reaction. In this study, a single atom Rh was added to the surface of Ni(111) by doping and adsorbing ways, and the performance of these surfaces was compared with the pure Ni(111) through density functional theory (DFT) calculation. The reactions related to the carbon formation were studied to obtain the favored adsorption site and dominant reaction paths on three surfaces. A good linear relationship between the charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 51 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…[24][25][26][27][28] For example, Y. Meng et al demonstrated that the doping of the Pd atom improved the thermodynamic stability and catalytic performance of the Cu(111) surface towards partial oxidation of methane than the single Pd atom adsorbed surface. 28 Similarly, Guo and coworkers 29 have recently shown that Rh doped Ni(111) catalyst exhibits promising performance for coke resistance in the CH 4 /CO 2 reforming reaction. Besides, the density functional theory calculations by Eisenberg and Baer have demonstrated that doping of Li atom on MgO signicantly eases the hydrogen abstraction reaction from methane.…”
Section: Introductionmentioning
confidence: 98%
“…[24][25][26][27][28] For example, Y. Meng et al demonstrated that the doping of the Pd atom improved the thermodynamic stability and catalytic performance of the Cu(111) surface towards partial oxidation of methane than the single Pd atom adsorbed surface. 28 Similarly, Guo and coworkers 29 have recently shown that Rh doped Ni(111) catalyst exhibits promising performance for coke resistance in the CH 4 /CO 2 reforming reaction. Besides, the density functional theory calculations by Eisenberg and Baer have demonstrated that doping of Li atom on MgO signicantly eases the hydrogen abstraction reaction from methane.…”
Section: Introductionmentioning
confidence: 98%